ON THE PRATT AND AIRY MODELS OF ISOSTATIC GEOID UNDULATIONS - Sjoberg L.E. (My University, 1998)
Usually the topographic-isostatic geoid undulation is derived by a downward continuation of the external potential to the geoid. Unfortunately, such an approach merely yields a fictitious potential at the continental geoid within the topographic masses. We show that the related bias may range to about 10 m based on the classical Pratt and Airy models for isostatic compensation.The above geoid contribution is generated by the topographic masses along the vertical to the computation point, i.e. it is a local contribution.Our second conclusion is that the isostatic geoid undulation also experiences a regional contribution from the surrounding topographic masses. This contribution is significant for extended high mountains and deep oceans.